1997
DOI: 10.1148/radiology.202.3.9051050
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodules: evaluation with US-guided core biopsy with an automated biopsy gun.

Abstract: To evaluate the efficacy of ultrasound (US)-guided automated core biopsy of thyroid nodules, 74 biopsies were performed in 61 consecutive patients with an 18-gauge short-throw (1.1-cm excursion) biopsy gun. Results were correlated with diagnoses made at surgery (n = 38) or at sonographic follow-up of at least 6 months (n = 36). Sensitivity, specificity, and accuracy of diagnoses made with automated core biopsy were 84%, 95%, and 91%, respectively. US-guided biopsy with an automated biopsy gun allowed accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 0 publications
1
35
0
1
Order By: Relevance
“…Sonographically guided thyroid nodule CB has been shown to be accurate, safe, and well tolerated (15,17,19,(26)(27)(28). There are several theoretical reasons why sonographically guided CB might be useful when thyroid nodule FNA is nondiagnostic: CB can provide more tissue than a nondiagnostic FNA and cellular architecture is retained, facilitating accurate histologic diagnosis (26,29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonographically guided thyroid nodule CB has been shown to be accurate, safe, and well tolerated (15,17,19,(26)(27)(28). There are several theoretical reasons why sonographically guided CB might be useful when thyroid nodule FNA is nondiagnostic: CB can provide more tissue than a nondiagnostic FNA and cellular architecture is retained, facilitating accurate histologic diagnosis (26,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Although core needle biopsies are widely used in other anatomic regions, relatively few series of US-guided core needle biopsy (CB) of thyroid nodules have been reported (16)(17)(18)(19)(20)(21). Current American Thyroid Association (ATA) thyroid Departments of 1 Radiology, 3 Pathology, 4 Surgery, and 6 Medicine; nodule management guidelines and the Society of Radiologists in Ultrasound Consensus Statement do not discuss the role of thyroid nodule core biopsy (CB) in the evaluation of thyroid nodules (8,12).…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies have compared thyroid FNA and CB, [9][10][11][12][13][14][15]28,29 to our knowledge, only 1 study 29 has described the practice of FNA followed by CB in nondiagnostic or suboptimal FNA cases during the same procedure. A few studies have reported higher accuracy with combined FNA/CB than with either procedure alone.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] To our knowledge, there are not enough studies to demonstrate the benefits of concurrent CB in improving the adequacy or accuracy of thyroid biopsy. Nearly all studies agree that the advantage of CB is providing adequate material for evaluation when such material is not readily available by FNA.…”
mentioning
confidence: 99%
“…10,21,22 In the modified capsular biopsy technique group, 1 patient had subsequent perinodular hemorrhage, which was resolved by manual compression. Perinodular hemorrhages infrequently occur even in FNA by using 23-to 25-gauge needles.…”
Section: Figmentioning
confidence: 99%